2009
DOI: 10.1007/s11130-009-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Hydrolysates from Germinated Soybean on Cancerous Cells of the Human Cervix: An In Vitro Study

Abstract: Consumption of soybeans can reduce the risk of different types of cancer. Little is known about the effect of germination on the anticancer properties of soya. This study was done to determine if germination improves the anticancer properties of soybean protein through generation of amino acids or bioactive peptides. Soybean was germinated for 0, 2, 3, 4, 5, and 6 days and proteins were isolated from the seeds. Isolates with and without ethanol-soluble phytochemicals were hydrolyzed with digestive enzymes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…This was due to natural proteolysis during germination [23], and also to changes in protein structure which facilitated enzyme access to the protein. Similar results have been reported by Mora-Escobedo et al [11].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This was due to natural proteolysis during germination [23], and also to changes in protein structure which facilitated enzyme access to the protein. Similar results have been reported by Mora-Escobedo et al [11].…”
Section: Resultssupporting
confidence: 92%
“…Peptides smaller than 1 kDa inhibited adipogenesis in the early differentiation stage, but the mechanism of action behind the phenomenon is not yet completely understood [33]. Germination produces several low-molecular weight peptides [11], which may explain the higher adipogenesis inhibition observed in the present study with hydrolysates from soybeans germinated for longer times (5 and 6 days).…”
Section: In Vitro Assaysmentioning
confidence: 66%
See 1 more Smart Citation
“…To assess if BPs are produced naturally during gastrointestinal digestion, in vitro digestions are commonly carried out with proteases (pepsin, trypsin, chymotrypsin, and pancreatin). Researchers have also performed enzymatic hydrolysis with microbial or plant enzymes, such as alcalase, flavourzyme, papain and bromelain, to obtain bioactive sequences [6,[11][12][13][14][15].…”
Section: Soybeansmentioning
confidence: 99%
“…This process generates changes in the secondary metabolite distribution and mobilizes the reserve proteins stored in the cotyledon protein bodies, producing intermediate molecular weight peptides. Mora-Escobedo, et al [15] showed that germination can improve the anti-proliferative effect of soybean protein on HeLa and C-33 cervical cancer cells. Peptides generated during germination can alter cell signaling pathways and cause apoptosis.…”
Section: Soybeansmentioning
confidence: 99%